Lived Traumatic Childbirth Experiences of Newly Delivered Mothers Admitted to the Postpartum Ward: a Phenomenological Study - Abdollahpour, Sedigheh (J Caring Sci, 2019)
Introduction: Childbirth is a stressful event in every woman's life, leading to traumatic deliveries in half of the cases. This study aimed at describing mothers’ lived experiences which make them perceive their childbirth as traumatic. Methods: In this descriptive phenomenological study, based on the DSM-V-A criteria, 32 mothers who had perceptions of a traumatic event during their labor and delivery were explored through semi-structured interviews, and the collected data were analyzed using the Colaizzi’s method. Results: Four main themes could be extracted from the experiences of the mothers. The first theme was sensational and emotional experiences followed by clinical experiences, legal experiences and human dignity, and environmental experiences. The sensational and emotional experiences included four main categories (anxiety, fear, sorrow, anger). The theme of clinical experiences included two main categories (avoidable and unavoidable childbirth complications). The theme of legal experiences and human dignity included two main categories (non-observance of the charter of patient rights, and non-observance of human rights). The theme of environmental experiences also included two main categories (lack of proper supervision and management). Conclusion: To prevent traumatic childbirth and its negative effects, different psychological aspects of childbirth need to be identified.